2014
DOI: 10.1074/jbc.m113.528224
|View full text |Cite
|
Sign up to set email alerts
|

Groove-type Recognition of Chlamydiaceae-specific Lipopolysaccharide Antigen by a Family of Antibodies Possessing an Unusual Variable Heavy Chain N-Linked Glycan

Abstract: Background: S25-26 displays remarkable specificity and avidity toward the unusual inner core LPS from Chlamydia. Results: Liganded and unliganded structures reveal bound antigen and significant ordered N-glycosylation on the variable heavy chain. Conclusion: Groove-type paratope recognizes the antigen in a manner distinct from all other Chlamydia-specific antibodies. Significance: Structural analysis of germ-line-coded antibodies provides insight to anaphylaxis induced by ␣-galactose (␣Gal) epitopes on therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 74 publications
1
31
1
Order By: Relevance
“…Thus, the enveloping capacity of antibody binding sites can allow for very specific recognition. 51,52 A range of experimental techniques, including synthetic chemistry, antibody engineering, microarray technology and NMR, alongside computational approaches have been key to elucidate molecular structural features that modulate glycan-antibody recognition. [53][54][55][56][57] In this regard, antibody engineering and molecular modelling have been applied to demonstrate that in both pyranoside-and furanoside-antibody systems, the affinity and specificity mostly rely on CH-p interactions.…”
Section: Figmentioning
confidence: 99%
“…Thus, the enveloping capacity of antibody binding sites can allow for very specific recognition. 51,52 A range of experimental techniques, including synthetic chemistry, antibody engineering, microarray technology and NMR, alongside computational approaches have been key to elucidate molecular structural features that modulate glycan-antibody recognition. [53][54][55][56][57] In this regard, antibody engineering and molecular modelling have been applied to demonstrate that in both pyranoside-and furanoside-antibody systems, the affinity and specificity mostly rely on CH-p interactions.…”
Section: Figmentioning
confidence: 99%
“…The common feature of the three HIV bnAb classes described is that the weak protein-carbohydrate interactions are overcome through multivalent binding to multiple glycans and protein residues within one Fab. Interestingly, crystal structures of Abs binding to other glycan antigens show whole saccharide units binding either within a pocket or groove [51, 52]. However, the majority of HIV glycan-binding bnAbs, with the exception of 2G12, bind across the face of the glycan [53].…”
Section: Hiv-1 Bnabs Target Envelope Glycansmentioning
confidence: 99%
“…Early studies showed that even highly specific induced IgM and IgG monoclonal antibodies used for cell typing (anti‐HLA, anti‐H2 and anti‐blood group antigens) were autopolyreactive . It was also established that almost all autopolyreactive NAAbs recognized conformational epitopes . Taking into consideration the above observations, the autopolyreactivity, as revealed by these techniques, could be related to the presence of various active binding sites situated in different spatial locations on the paratopes of antibodies that probably take part in the recognition of three dimensional structures.…”
Section: Humoral and Cellular Features Of Naabsmentioning
confidence: 99%